A Meta‐Analysis of Therapeutic Pain Neuroscience Education, Using Dosage and Treatment Format as Moderator Variables. Issue 3 (22nd November 2020) - Romm, Marnin Joseph; Ahn, Soyeon; Fiebert, Ira; Cahalin, Lawrence Patrick
Abstract: Objectives: This meta‐analysis aimed to assess the overall effect of therapeutic pain neuroscience education (TPNE) on chronic musculoskeletal pain and to further assess whether such an effect differs by TPNE dosage as well as other treatment format components. Dosage included the number of TPNE sessions provided as well as the amount of time per TPNE session. Structural components included TPNE provided alone as treatment or combined with other pain management modalities, as well as the inclusion of group‐based treatment sessions. Methods: Electronic databases were utilized to search for randomized controlled trials that included TPNE. The overall effectiveness of TPNE was estimated on 4 pain outcome measures, including kinesiophobia, pain intensity, pain disability, and pain catastrophizing. The differential effectiveness of TPNE was examined using a mixed‐methods moderator analysis on various study‐level characteristics to identify potential moderators affecting the overall results. Results: Significant effects of TPNE were found on all the outcome measures. The only moderator that displayed a significant effect was group‐based treatment on kinesiophobia ( z  = −2.23, P  < 0.05, 95% confidence interval [CI] −2.70 to −0.20). Between‐group analysis revealed that only interventions that included group sessions were found to be statistically significant ( z  = 2.20, P  < 0.05) and displayed a large effect size ( d  = 0.80, 95% CI 0.09 to 1.50). Discussion: Therapeutic pain neuroscience education had a statistically significant impact on all the explored pain outcome measures. However, when investigating the treatment dosage and format moderator variables, they appeared to not have a statistically significant effect except for group‐based interventions on kinesiophobia levels. Conclusion: This meta‐analysis examined the efficacy of TPNE for patients with chronic pain. It assessed various pain outcome measures following intervention. In addition, this research identified that various moderator variables do not have and do have an impact on the treatment modality of TPNE.